OPTIMALISASI DUKUNGAN KELUARGA DALAM PERAWATAN BAYI BERAT BADAN LAHIR RENDAH (BBLR) DI RUMAH - Ayut Merdikawati; Asti Melani Astari; Muladefi Chioriyah; Nurul Evi; Laily Yuliatun; Niken Ummu Raehana; Azizha Adila Fitri (Caring : Jurnal Pengabdian Masyarakat, 2021)
Caring for LBW babies at home is must be intensively. One of the methods used is Kangaroo Mother Care (KMC) by providing warmth to LBW babies. Family involvement in the care of LBW babies is a very important. This community service aims to optimize the support of family in the care of LBW babies. Team members conducted this activity in Februari-Mei 2020 with the home visit & counseling method. Participants in this activity were 25 mothers who gave birth to LBW babies and who live in Malang Raya. Data Collection used questionnaires. The result of this activity, the majority of family support in the care of LBW babies was in good category (76%). In conclusion, family support plays an important role in the sustainability of the implementation of KMC at home.